New South Slavic Translations of Aesop’s Fairy Tales - Walczak-Mikołajczakowa, Mariola (Poznańskie Studia Slawistyczne, 2018)
In 2006 for the first time after more than 30 years a new translation of Aesop’s fairy tales into Bulgarian by Vladimir Atanasov was published. Aesop’s tales were also translated into Macedonian for the first time (by Valerij Sofronievski) and published in 2008. The article contains discussion and comparison of both translations. A collection of both volumes and classic editions of Aesop’s tales were described and translations were made from them. The authoress precedes her arguments with a short outline of the history of Aesop’s translations into Bulgarian. Particular attention is paid to the translation of bishop Sofroni from the early 19th century, because both discussed contemporary translations clearly refer to this work.